Dermatological Side Effects of Sildenafil among a group of Iraqi Males - Matloob, Nadheer A. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Sildenafil is a drug that is used to treat erectile dysfunctions, it acts by inhibiting CGMP specific phosphodiesterase type 5, an enzyme that regulates blood flow in the penis. The most common adverse effects of sildenafil are headache, dyspepsia, nasal congestion and impaired vision which includes photophobia and blurred vision. Many dermatological side effects are present like flushing, urticaria, sweating and many others.Patients and Methods: Fifty six males were included in this study, with ages between 37 – 60 years and a mean age of 50.1 ± 7.1years. The study was conducted from November 2004 till May 2009 in the Department of Dermatology of Al-Kadhymia Teaching Hospital in Baghdad; all patients experienced dermatological side effects every time they use the drug. Full history and full examination including dermatological examination were done for all patients.Results: The commonest dermatological side effect was flushing of the face which was seen in 44 (78.6%) patients followed by hyperhydrosis which was seen in 14 (25%) patients then urticaria which was seen in 12 (21.4%) patients. It is seemed that side effects were more with 100mg dose than with 50mg dose (78 side effect against 22 one) and this result was statistically significant.Conclusion: Dermatological side effects of sildenafil are fairly common and dermatologist must be aware of these side effects especially when he searches for the cause of angioedema, urticaria, pruritis as well as erythroderma.